Myanmar Economic Monitor, December 2018 : Navigating Risks - World Bank Group (World Bank, Washington, DC, 2018)
Myanmar's economy is navigating significant uncertainty and risks at home and abroad. A year after violent upheaval in Rakhine State led to the forced displacement of over seven hundred thousand refugees to Bangladesh, limited progress has been made in resolving fundamental issues relating to rights, repatriation and recovery. Global economic and trade prospects have also become more uncertain. Myanmar's economic growth is expected to slow from 6.8 percent in 2017/18 to 6.2 percent in 2018/19, which is still robust by regional and global standards. Macroeconomic volatility has intensified since the May 2018 Myanmar Economic Monitor, with inflation breaching two-year highs in August 2018, and the kyat depreciating by 18 percent against the U.S. dollar since April. Growth is projected to recover to 6.6 percent by 2020/21, helped by recent policy changes such as the adoption of the Myanmar Sustainable Development Plan, liberalization of wholesale and retail trade, implementation of the Myanmar Companies Law and large investments in infrastructure projects including those related to the Belt and Road Initiative. Risks to the outlook are tilted to the downside due to the possibility of a global slowdown in trade, domestic macroeconomic imbalances, and the loss of trade-related preferences to the European Union.